Non-Claimant States Perspectives On The South China Sea Dispute - Rusmuliadi Rusmuliadi (Faculty of Law Universitas Lampung, 2023)
The problem in the South China Sea is becoming increasingly complex because other parties outside the claimant country also fight for their regional interests. The other party was later called a non-claimant state in the South China Sea area. The main purpose of these non-claimant states is to ensure that international law of the sea is enforced in any part of the sea on the planet. The main reason is to ensure safety and freedom to cross this route, the main sea route for transporting various goods and commodities with high economic value. In general, these non-claimant states oppose China's actions that do not follow the agreed UNCLOS. The juridical normative research methods with literature studies present the legal basis for the actions of non-claimant states in the South China Sea region. This study describes the basis of international law as well as the interests and policies of non-claimant states such as Indonesia, the USA, the UK, Australia, the EU, Japan, and India over the South China Sea region, which is most active in showing their attention to the dynamics in the South China Sea.